2009
DOI: 10.1016/j.jpain.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A Prolonged Nitric Oxide-Dependent, Opioid-Mediated Antinociceptive Effect of Hyperbaric Oxygen in Mice

Abstract: Hyperbaric oxygen (HBO 2 ) therapy is reported to cause pain relief in several conditions of chronic pain. A single 60-min session of HBO 2 treatment produced a prolonged antinociceptive effect in mice that persisted for 90 min after cessation of treatment. The HBO 2 -induced antinociception was significantly attenuated by pretreatment prior to HBO 2 exposure with the opioid antagonist naltrexone, the non-specific nitric oxide synthase (NOS)-inhibitor N G -nitro-L-arginine methyl ester (L-NAME) and the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 23 publications
4
53
2
1
Order By: Relevance
“…We also found that inhibiting either the activity or the expression of nNOS can interfere with the antinociceptive effect of HBO 2 following 11- and 60-min treatments. This suggests that NO initiates a process that culminates in the relief of pain (Ohgami et al, 2009; Zelinski et al, 2009) in the experimental pain model used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that inhibiting either the activity or the expression of nNOS can interfere with the antinociceptive effect of HBO 2 following 11- and 60-min treatments. This suggests that NO initiates a process that culminates in the relief of pain (Ohgami et al, 2009; Zelinski et al, 2009) in the experimental pain model used.…”
Section: Discussionmentioning
confidence: 99%
“…This nociceptive model was selected over tests employing a thermal noxious stimulus because this paradigm is significantly more sensitive to detection of κ opioid antinociceptive activity than are thermal tests (Tyers, 1980) and because our previous studies have implicated κ opioid mechanisms in mediation of HBO 2 -induced antinociception (Zelinski et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for selection of 5.0 mg/kg of naloxone as our dose for precipitating withdrawal was a previous finding from our laboratory that HBO 2 -induced antinociception in rodents was sensitive to antagonism by both opioid antagonist drugs as well as rabbit antisera against selected endogenous opioid peptides, namely dynorphin [Zelinski et al ., 2009; Heeman et al ., 2013; Gibbons et al ., 2013]. This suggests that a mechanism of HBO 2 -induced antinociception is stimulation of neuronal release of opioid peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that HBO 2 produced an antinociceptive effect in mice that was dependent on both nitric oxide (NO) and opioid receptors [Zelinski et al ., 2009]. Further studies suggested that HBO 2 might be capable of stimulating neuronal release of endogenous opioid peptides [Heeman et al ., 2013].…”
Section: Introductionmentioning
confidence: 99%